Antibacterial Properties of a Novel Zirconium Phosphate-Glycinediphosphonate Loaded with Either Zinc or Silver - Campoccia, Davide (Materials (Basel), 2019)
A novel compound consisting of a zirconium phosphate-glycinediphosphonate (ZPGly) has recently been introduced. This 2D-structured material forming nanosheets was exfoliated under appropriate conditions, producing colloidal aqueous dispersions (ZPGly-e) which were then loaded with zinc (Zn/ZPGly) or silver ions. Silver ions were subsequently reduced to produce metallic silver nanoparticles on exfoliated ZPGly nanosheets (Ag@ZPGly). In the search for new anti-infective materials, the present study investigated the properties of colloidal dispersions of ZPGly-e, Zn/ZPGly, and Ag@ZPGly. Ag@ZPGly was found to be a bactericidal material and was assayed to define its minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) on the five most prevalent pathogens of orthopaedic implant infections, namely: Staphylococcus aureus ATCC25923, Staphylococcus epidermidis RP62A, Enterococcus faecalis ATCC29212, Escherichia coli ATCC51739, and Pseudomonas aeruginosa ATCC27853. MIC and MBC were in the range of 125–250 μg/mL and 125–1000 μg/mL, respectively, with E. coli being the most sensitive species. Even colloidal suspensions of exfoliated ZPGly nanosheets and Zn/ZPGly exhibited some intrinsic antibacterial properties, but only at greater concentrations. Unexpectedly, Zn/ZPGly was less active than ZPGly-e.